Fatigue Performance of Steel–UHPC Composite Bridge Deck System with Large Longitudinal Rib - Yi Zhou; Chuan Wei; Guoxi Liang; Dequan Zhou (Advances in Materials Science and Engineering)
A critical problem in the development and application of orthotropic steel bridge decks (OSDs) is fatigue cracking, which is determined by the deck’s structural system, mechanical characteristics, load, and external environmental factors. The development of bridge deck systems with high fatigue resistance is increasingly gaining interest in the field of bridge deck design. An effective method for improving the fatigue life of OSDs is the introduction of an ultra high performance concrete (UHPC) layer to enhance OSD’s stiffness. In this study, two types of experiments were performed to investigate the transverse and longitudinal fatigue behaviors of a steel–UHPC composite bridge deck with large longitudinal ribs. The experiments show that the application of a 70-mm-thick UHPC layer effectively reduces the stress intensity at key fatigue details in OSDs. The influence of the UHPC layer on the OSD fatigue performance was evaluated by experiments and finite element analysis. After the formation of microcracks on the UHPC surface layer, the composite bridge deck system continued to exhibit adequate fatigue performance. Moreover, the effects of damage accumulation on the UHPC layer and studs in transverse specimens were evaluated.